أثر الإفصاح الاختياري للمعلومات البيئية في جودة المعلومات المحاسبية لمنظمات الأعمال السودانية - محمد عمر; الغصين راغب (Latakia University Journal - Economic and Legal Sciences Series, 2018)
تمثلت مشكلة الدراسة في التساؤل حول ما إذا كان الإفصاح الاختياريعن المعلومات البيئية يؤدي إلى جودة المعلومات المحاسبية بمنظمات الأعمال السودانية. هدفت الدراسة إلى معرفة مدى التزام المنشآت السودانية بالأداء البيئي والإفصاح عن ذلك في التقارير المالية، وتحليل العلاقة بين الإفصاح الاختياري عن المعلومات البيئية وجودة المعلومات المحاسبية وتقويم الالتزام البيئي في منظمات الأعمال السودانية.وتمتوزيع عدد 150 استمارة استبانة على مكاتب المراجعة العاملة في السودان وكان الصالح منها للتحليل 130 استمارة، وتوصلتالدراسة إلى أنه يُؤدي الإفصاح الاختياري عن المعلومات البيئية في التقارير المالية لمنظمات الأعمال السودانية إلى مصداقية معلومات التقارير المالية ويُوفر معلومات مفيدة لاتخاذ القرارات، ويُمكن من التنبؤ بالمخاطر البيئة ويدل على إدراك منظمات الأعمال للقضايا البيئية. The study problems represented in the question if it is possible that optional disclosure of environmental information will leads to the quality of accounting information in Sudanese business organizations. The study aimed to know whether the Sudanese bodies committed to environmental performance and disclosure in financial reports & the analysis of the relationship between the optional disclosure & the environmental information to the quality of accounting information and evaluation of the environmental committing in Sudanese business organizations. In this study, a number of 150 questionnaires forms are distributed among accounting offices that work in Sudan. About 130 questionnaires forms are valid for analysis. The study comes the result that the optional disclosure leads to environmental information in the financial reports &provide good information in taking decisions& enable to predict environmental risk, which indicate the awareness of business organizations to the environmental issues.